El proceso enseñanza - aprendizaje y su incidencia en el desarrollo de la creatividad de los estudiantes de primer año de educación general básica de la Escuela Fiscal Mixta Alejandrino Velasco”, período lectivo 2011 – 2012”. Lineamientos alternativos - Paladines Rodríguez, Melania Lucia (2013)
Creativity within the educational environment is very important since it meets the paper to support the teaching - learning process, this paper is entitled: "The teaching - learning process and its impact on the development of creativity of freshmen General Basic Education School Joint Fiscal Alejandrino Velasco "school year 2011-2012. Alternative Guidelines, and the overall objective: To contribute to improve the quality of education by establishing the impact of the teaching-learning in the development of creativity of students in the first year of basic education in the city of Loja. The specific hypotheses that have guided this research are: 1) predominantly affects education in developing creativity among freshmen basic education school Joint Fiscal Alejandrino Velasco, of the city of Loja, school year 2011 - 2012, 2) predominantly affects learning in developing creativity among freshmen basic education school Fiscal Joint Alejandrino Velasco, of the city of Loja, school year 2011-2012. The processes used were the hypothetical - deductive, explanatory analytical, statistical, in addition to the development of the analysis came to the descriptive method. The techniques was applied to interview the principal, teachers survey and observation to teaching - learning process of children / as first-year basic education through the interview guide, questionnaire and observation guide designed for effect. The research involved one authority, 2 teachers and 50 children / as the educational establishment. The main results which are reached: Teachers know the teaching-learning process and the constructivist model, but do not apply it, the teachers do not apply variety of strategies and techniques in daily activities that help develop creativity in children, another important result is that teachers know little about creativity and how to develop in children / as, which is negatively affecting the normal development of the teaching - learning process.